Face mask correlation with allergic rhinitis symptoms severity during COVID‐19 pandemic: A cross‐sectional study - Hossein Esmaeilzadeh; MReza Goodarzian; Alireza Abbasi; Mohammad Alamdari; Negar Mortazavi (Health Science Reports, 2023)
Abstract Background Face mask is the first line to protect the respiratory mucosa from the coronavirus particles in aerocells and droplets and without this, the exposure of the mucosa to the virus and allergens trigger the immune and inflammatory system. These lead to Allergic Rhinitis (AR) symptoms or virus infection. Aim This study discusses about the effects of face mask on the severity of AR symptoms using the Sino‐Nasal Outcome Test (SNOT‐22) in AR cases during the Corona Virus Disease 2019 (COVID‐19) pandemic. Method In this cross‐sectional study, 54 cases previously diagnosed as moderate and severe AR based on Allergic Rhinitis and its Impact on Asthma and Visual Analog Scale score referred to the tertiary allergy clinic were involved, while 5 of them were excluded. AR symptoms before and during the pandemic were compared based on the SNOT‐22 questionnaire. Demographics, AR severity, and comorbidities were registered. Results The mean age was 31.4 ± 13.5 years with the male−female ratio of 1.4. The mean SNOT‐22 score was 36.1 ± 20.3 before and 29.5 ± 16.8 during the pandemic. Although 36.7% (n: 18) of all participants had severe symptoms before the pandemic, 10.2% (n: 5) had severe AR symptoms during the pandemic. 53.0% (n: 26) of patients had moderate AR symptoms, and 36.7% (n: 18) had mild AR symptoms in the pandemic. There was no significant difference between each paired subgroup in AR symptom changes but the symptom improvement was significant in most of the subgroups when compared to the pre‐pandemic period. Smoking had an adverse effect on AR symptoms (p: 0.034). Conclusion Face mask affects the quality of life in AR patients and improves the severity of AR symptoms during COVID‐19 pandemic. Smoking worsens this severity. Age, gender, pet ownership, underlying conditions, and previous COVID‐19 infection were not associated with AR symptoms severity and alteration in the AR individuals' quality of life during the COVID‐19 pandemic.